Microbial dysbiosis precedes signs of sea star wasting disease in wild populations of Pycnopodia helianthoides - McCracken, Andrew R.; Christensen, Blair M.; Munteanu, Daniel; Case, B. K. M.; Lloyd, Melanie; Herbert, Kyle P.; Pespeni, Melissa H. (Frontiers in Marine Science, 2023)
Sea star wasting (SSW) disease, a massive and ongoing epidemic with unknown cause(s), has led to the rapid death and decimation of sea star populations with cascading ecological consequences. Changes in microbial community structure have been previously associated with SSW, however, it remains unknown if SSW-associated dysbiosis is a mechanism or artifact of disease progression, particularly in wild populations. Here, we compare the microbiomes of the sunflower sea star, Pycnopodia helianthoides, before (Naïve) and during (Exposed and Wasting) the initial outbreak in Southeast Alaska to identify changes and interactions in the microbial communities associated with sea star health and disease exposure. We found an increase in microbial diversity (both alpha and beta diversity) preceding signs of disease and an increase in abundance of facultative and obligate anaerobes (most notably Vibrio) in both Exposed (apparently healthy) and Wasting animals. Complementing these changes in microbial composition was the initial gain of metabolic functions upon disease exposure, and loss of function with signs of wasting. Using Bayesian network clustering, we found evidence of dysbiosis in the form of co-colonization of taxa appearing in large numbers among Exposed and Wasting individuals, in addition to the loss of communities associated with Naïve sea stars. These changes in community structure suggest a shared set of colonizing microbes that may be important in the initial stages of SSW. Together, these results provide several complementary perspectives in support of an early dysbiotic event preceding visible signs of SSW.